Cytomorphological identification of advanced pulmonary adenocarcinoma harboring KRAS mutation in lymph node fine‐needle aspiration specimens: Comparative investigation of adenocarcinoma with KRAS and EGFR mutations. Issue 7 (26th November 2014) - Song, Dae Hyun; Lee, Boram; Shin, Yooju; Choi, In Ho; Ha, Sang Yun; Lee, Jae Jun; Hong, Min Eui; Choi, Yoon‐La; Han, Joungho; Um, Sang‐Won
<x xml:space="preserve">Abstract</x> Background Kirsten rat sarcoma 2 viral oncogene homolog (KRAS) mutation in pulmonary adenocarcinoma is clinically important due to its association with resistance to EGFR inhibitors and poor prognosis. To our knowledge, there has not been a comparative study focusing on cytological nuclear features of pulmonary adenocarcinoma harboring KRAS mutation (KRAS‐AD). Hence, we compared the cytomorphology of metastatic KRAS‐AD and EGFR‐positive adenocarcinoma (EGFR‐AD) in aspiration specimens from lymph nodes. Methods Forty lymph node aspiration specimens from forty KRAS‐AD patients were collected at Samsung Medical Center (Seoul, Korea) from 2009 to 2013. As a control group, 40 EBUS‐FNA lymph node specimens from 20 EGFR‐AD patients were collected. EGFR‐AD specimens were evaluated at Samsung Medical Center (Seoul, Korea) from 2012 to 2013. All 80 specimens were histologically confirmed to metastatic adenocarcinoma. Two pathologists performed a blinded review of all specimens. Results Compared with EGFR‐AD, KRAS‐AD exhibited more severe nuclear pleomorphism (P < 0.001), coarse chromatin (P = 0.001), cherry‐red nucleoli (P < 0.001) and naked tumor cells (P = 0.002) with necrotic (P < 0.001) and neutrophilic (P = 0.008) background. Conclusions Our study provides the first demonstration of cytomorphologic differentiation between metastatic KRAS‐AD and metastatic EGFR‐AD in lymph node aspiration specimens. Diagn. Cytopathol. 2015;43:539–544. © 2014 Wiley Periodicals, Inc.